Maturity status of youth football players: A noninvasive estimate - Malina, R. M.; Cumming, S. P.; Morano, P. J.; Barron, M.; Miller, S. J. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To estimate the biological maturity status of youth football players 9-14 yr old using a noninvasive method and to compare the body size of players of contrasting status.